Bone Marrow Progenitor Cells Isolated from Young Rabbit Trochlea Are More Numerous and Exhibit Greater Clonogenic, Chondrogenic, and Osteogenic Potential than Cells Isolated from Condyles. (October 2018) - Dwivedi, Garima; Chevrier, Anik; Hoemann, Caroline D.; Buschmann, Michael D.
Objective . Bone marrow stimulation procedures initiate repair by fracturing or drilling subchondral bone at base of cartilaginous defect. Earlier studies have shown that defect location and animal age affect cartilage repair outcome, suggesting a strong influence of structural and biological characteristics of subchondral bone. Here, we analyzed comprehensive biological characteristics of bone marrow progenitor cells (BMPCs) in subchondral bone of young and old rabbit condyle and trochlea. We tested the hypothesis that in vitro biological properties of BMPCs are influenced by location, age of donor and method of their isolation. Design. In vitro biological properties, including cell yield, colony-forming unit fibroblasts (CFU-f), surface marker expression, and differentiation potential were determined. Comparisons were carried out between trochlea versus condyle and epiphyseal versus metaphyseal bone using old ( N = 5) and young animal knees ( N = 8) to generate collagenase and explant-derived BMPC cultures. Results . CFU-f, cell yield, expression of stem cell markers, and osteogenic differentiation were significantly superior for younger animals. Trochlear subchondral bone yielded the most progenitors with the highest clonogenic potential and cartilaginous matrix expression. Trochlear collagenase-derived BMPCs had higher clonogenic capacity than explant-derived ones. Epiphyseal cells generated a larger chondrogenic pellet mass than metaphyseal-derived BMPCs. All older pellet cultures and one non-responder young rabbit failed to accumulate glycosaminoglycans (GAGs). Conclusion . Taken together, these results suggest that properties intrinsic to subchondral progenitors could significantly influence cartilage repair potential, and could partly explain variability in cartilage repair outcomes using same cartilage repair approach.